Synthesis of PEGylated Human Serum Albumin by Maleimide-Thiol Chemistry and Histopathological Evaluation in a Mice Model of Carrageenan-Induced Inflammation - Mehdi Hoorang; Alimohammad Tamaddon; Gholamhosein Yousefi (Shiraz University of Medical Sciences, 2019)
Occasional incompetence of human serum albumin (HSA) as a plasma expander is linked to severity of the underlying endothelial cell injury so that HSA can readily extravasate if structural integrity of the endothelial is compromised. Consequently, the leaking HSA may exacerbate the oncotic plasma gradient and results in capillary leak syndrome; therefore, we hypothesized that HSA modification by the covalently attaching multiple PEG (polyethylene glycol) groups would result in enhanced retention of HSA in blood circulation in animal model of acute inflammation. PEGylation of HSA was performed by maleimide-thiol chemistry. The products were characterized by polyacrylamide gel electrophoresis and size-exclusion chromatography. Extravasation of PEGylated HSA was compared to the native protein in BALB/C mice model of carrageenan-induced inflammation by histopathological evaluations. HSA was thiolated by either reaction of 2-iminothiolane (Traut's reagent) with lysine side chains or DTT reduction of disulfide bridges for subsequent reaction with methoxyPEG-maleimide (mPEG-Mal). The PEGylation reaction was optimized in terms of pH and mPEG/HSA molar ratio, producing high conjugation yield. mPEG 5 KDa-HSA demonstrated higher osmotic pressure and more homogeneous weight distribution than mPEG 20 KDa-HSA. According to the histopathological findings, mPEG 5 KDa-HSA showed lower extravasation in comparison to native HSA in carrageenan-induced inflammation model. Conclusively, PEGylated form of HSA might lessen the need of frequent HSA administration via decreasing the capillary leakage and endow a product with improved intravascular retention.